Tasawwuf (Sufism) as The Basis for Internalizing Humanist Character of Indonesian Muslims (Case Study of Pesantren in Yogyakarta and Madura) - Muhammad Itsbatul Haq (Universitas Islam Negeri Sunan Kalijaga, 2019)
Violence in Islam could be caused by many factors. However, the main problem of the violent occurance is a lack of humanity. This research shows that tasawwuf (sufism) arguably has profoundly contributed to the making of Indonesian Islam which is humanist and inclusive. This research seeks to examine the role of tasawwuf in shaping the humanist character of santri (students of pesantren), in two pesantrens (Islamic boarding school) in Indonesia, which are Pondok Pesantren Krapyak, Yogyakarta, and Pondok Pesantren Annuqayah, Madura. The first object is a representation of pesantren in heterogeneous area in which various ethnic groups, religious and cultural communities live, the latter is a representation of pesantren in homogeneous region where Islam is much more dominant and consists of one ethnic group, speak the same language, and share similar culture. This research focuses on the impacts of tasawwuf teaching in the process of the internalization of santris’ humanist character in these two particular pesantren. The method of this research is an observation and in-depth interview with phenomenological approach. The result shows that the two pesantrens utilize al-Ghazali's tasawwuf literature as the main reference for the teaching process, and it was proven to be a huge part in internalizing humanist character for santris in general. There are two great values that can be learned from the tasawwuf teachings in shaping this humanist character. First, the perception of God. Tasawwuf perceives God as the Mighty and Merciful entity. This perception is originated from the concept of raja’ (hope), tawbah (repentance), and rahmah (mercy). The second is the perception of human beings. Humans are understood as dynamic entities. The concept of su' al-khatimah (bad end to life) and husn al-khatimah (good end to life) plays a vital role in leading santris’ notion in opposing any form of violence.